A 10 GHz Compact Balun with Common Inductor on CMOS Process - Pakasiri, Chatrpol; Xu, Jian Long; Wang, Sen (My University, 2023)
This paper presents a compact balun with a common inductor design. The design used Wilkinson-type balun topology with modified lumped transmission lines and a common inductor to realize circuit size reduction on a lossy CMOS process. Measurements of the prototype chip had a reflection coefficient below 17.8 dB at all ports, an insertion loss of 1.98 dB, and an isolation of 16.8 dB. The chip size was only 0.025λ0 × 0.034λ0.
Keywords: CMOS; common inductor; lumped transmission line; Wilkinson-type balun